2014
DOI: 10.1016/j.jadohealth.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Substance Use Among Vulnerable Adolescents in Five Cities: Findings From the Well-Being of Adolescents in Vulnerable Environments Study

Abstract: Introduction Adolescent substance use has numerous consequences. Our goals in this paper are to compare the prevalence and correlates of substance use among ethnically diverse adolescents. Methods Data are from 2332 adolescents aged 15 – 19 years recruited via respondent driven sampling from disadvantaged settings in five cities. Multivariate logistic regression was used to identify correlates of current substance use. Results About half of the respondents were male. Most adolescents (73.4%) were currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
8
26
0
Order By: Relevance
“…It is possible, therefore, that given the low-income status of most study respondents; older adolescents may be more responsible for assisting with earning income for the family. As a result, increased age and financial stresses may be contributing to substance use in this population, as shown in previous studies of adolescents [24].…”
Section: Discussionsupporting
confidence: 57%
“…It is possible, therefore, that given the low-income status of most study respondents; older adolescents may be more responsible for assisting with earning income for the family. As a result, increased age and financial stresses may be contributing to substance use in this population, as shown in previous studies of adolescents [24].…”
Section: Discussionsupporting
confidence: 57%
“…19 According to other studies, 57%-70% of homeless youth reported recent use of alcohol, 20 57%-68% reported recent use of marijuana, 20 and 50% reported prescription drug misuse, 21 rates that are higher than those found in the general population. 22 Homeless youth report using substances to attenuate the negative psychological effects of living on the streets, to reduce depressive symptoms, and to stay awake when they experience difficulty finding a safe place to sleep. 19 Homeless youth are also less likely to seek treatment for substance use compared with housed youth.…”
mentioning
confidence: 99%
“…Latkin et al, 1999; Carl A. Latkin et al, 1995; Linas et al, 2015; Linton et al, 2014; Matto et al, 2007; Mennis & Mason, 2010; Olumide et al, 2014; Sterk et al, 2014; Williams & Latkin, 2007). Substance users, however, may “select” the type of neighborhoods where they live and choose the type of people with whom they interact.…”
Section: Introductionmentioning
confidence: 99%
“…Latkin et al, 1999; Carl A. Latkin et al, 1995; Linas et al, 2015; Matto et al, 2007; Mennis & Mason, 2010; Olumide et al, 2014; Williams & Latkin, 2007) are the most widely documented contextual correlates of illicit drug use. Theories of social causation and social influence, which suggest that neighborhood and social network characteristics are distal causes of illicit drug use, have been used to provide explanations of the mechanisms behind these relationships.…”
Section: Introductionmentioning
confidence: 99%